Rules for publication - Information for authors - Editorial, Consejo (2018)
Contributions that are approved for publication will go through the final editing process. The proofs of printing will be presented to the authors for the respective control. The changes that can be made will only be in correction of style, correction of English, but not of content. The proofs must be returned within a maximum period of seven days by the authors, or otherwise the final version will be accepted.